(untitled) (Razi Medical Journal, 2025)
Acute appendicitis remains a common surgical emergency with significant variability in presentation and management outcomes across different populations. This study examines the demographic characteristics, diagnostic approaches, and surgical outcomes of acute appendicitis in a Libyan cohort, with particular focus on the Alvarado Score, inflammatory markers, and comparative effectiveness of laparoscopic versus open appendectomy. A retrospective analysis was conducted on 93 patients who underwent appendectomy between June 2024 and December 2024 at Alkahdera hospital in Tripoli, Libya. Data collected included demographic variables, Alvarado Scores, comorbidities, surgical approaches, length of hospital stay, and complication rates. Inflammatory markers (CRP and NLR) were analyzed for their correlation with disease severity. The majority of cases occurred in young adults aged 18–29 years (53.8%), with a male predominance (62.4%). The Alvarado Score demonstrated good diagnostic utility, with 52.7% of patients scoring in the high-probability range (7–8); however, 12.9% of confirmed cases had low scores (1–4). Laparoscopic appendectomy (64.5%) was associated with shorter hospital stays (2.9 vs. 4.1 days, p<0.05) and lower complication rates (6.7% vs. 15.2%) compared to open surgery. Elevated CRP (89.5 mg/L) and NLR (9.2) were strongly associated with perforated/gangrenous appendicitis, which had a 33% complication rate versus 6% in uncomplicated cases. This study confirms the predominance of appendicitis in young Libyan males and supports the use of the Alvarado Score as a diagnostic tool, while highlighting its limitations in low-score cases. Laparoscopic appendectomy demonstrated superior outcomes, reinforcing its role as the preferred approach when feasible. Inflammatory markers effectively predicted disease severity, suggesting their potential utility in risk stratification. These findings provide valuable insights for optimizing appendicitis management in similar resource-constrained settings.